Certain factors that affect the food habits of 6 nursery school children as observed in the child development laboratory of the U.P. Second semester, 1957-1958 - Ejercito, Ma. Josefa Ferriols 1935-; Corpuz, Aurora Garcia (1959)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (M.H.E.)--University of the Philippines, Diliman.
Keywords: Children -- Care and hygiene